(untitled) (Journal of actual problems of jurisprudence, 2018)
This article examines the presumption of innocence in criminal proceedings. The presumption of innocence of the accused has an important place in the implementation of the criminal proceedings. The presumption of innocence protsessualisty are constant discussions that relate to its logical and political nature, as enshrined in the law and implementation mechanism tion. The presumption of innocence must "work" and when applied to the defendant procedural enforcement in a preliminary investigation. Keywords: The presumption of criminal proceedings, the investigator, the proof.